Pengaruh Penggunaan Media Televisi Dan Terpaan Iklan Terhadap Perilaku Konsumtif Mahasiswa Eksekutif Stikom Interstudi - Poppy Ruliana; Nyoman Puspadarmaja (Inter Komunika, 2016)
The main subject in this research is studying the effects of the advertising impact of the Nokia cellular phone advertising against the consumerism effect on executive students of STIKOM InterStudi, Jakarta. Nokia’s TV commercials are appearing in many kinds of types and models, encouraging changing to new models or types becoming as a consumptive behavior. The objective of the research is to studying and analyzing “The Effect of Advertising of Nokia Mobile Phone on Television Media against The Consumptive Behavior of The Executive Students of The Department of Public Relations at STIKOM InterStudi”.  The communication models and theories in this research are based on the effects of advertising messages from Wendell Johnson and the consumptive behavior model of Henry Assael.  The research method is following the explanatory method survey. The population is the executive students at STIKOM InterStudi, Jakarta. The sampling is using the purposive sampling technique. Data compilation is through observation, questionnaires, interview, documentation and literature studies. Quantitative analysis is following the path analysis plus qualitative data. The overall result shows that the Nokia advertising in the television media has been proven that it effected on the executive students’ at STIKOM InterStudi, consumptive behavior.